Impact Pengaruh Intervensi Aplikasi “Anem SIP” Terhadap Pengetahuan, Perilaku Kepatuhan Mengomsumsi Tablet Tambah Darah dan Kadar Hemoglobin Pada Remaja Putri: Quasy Experiment: The Effect of the “Anem SIP” Application Intervention on Knowledge, Adherence to Iron Tablet (TTD) Consumption, and Hemoglobin Levels in Female Adolescents: A Quasi-Experimental Study - Sarinah Siregar; Witi Karwiti; Agraini; Egy Sunanda Putra; Larasti Putri Umizah (Universitas Airlangga, 2026)
Background: Anemia among women of reproductive age is a significant public health problem, with a global prevalence of 30% according to the 2021 World Health Organization (WHO) data. Although the iron tablet (TTD) supplementation program has been implemented, consumption coverage remains suboptimal due to low adherence and limited knowledge, affecting 18% of female adolescents in Indonesia. This low adherence is influenced by several factors, including forgetfulness, perception that supplementation is unnecessary, or consumption only during menstruation. At the policy level, the challenges are further increased by the distribution of TTD by health workers to schools without adequate follow-up. Objectives: This study aims to determine the effect of the Anem SIP application intervention on knowledge, adherence to TTD consumption, and hemoglobin (Hb) levels in female adolescents. Methods: A quasi-experimental study with a pretest-posttest design and no control group was conducted among 138 female adolescents at the Tangkit and Olak Kemang Community Health Centers in Muaro Jambi Regency in 2024. Data collection used a valid questionnaire to assess knowledge, while adherence to TTD consumption was determined through the Anem SIP application. Hb levels were measured using a hematology analyzer at the Jambi Ministry of Health Polytechnic Laboratory. Subsequently, data were analyzed using the Wilcoxon test with a 95% confidence interval. Results: The results showed that there was an increase in average knowledge from 56% to 87%, while adherence to TTD consumption improved before and after the intervention. Laboratory tests showed an increase in Hb levels from 12.4 g/dl to 13.3 g/dl. This study found a significant difference in knowledge and Hb levels between pre- and post-treatment. Conclusions: The implementation of the Anem SIP application showed the potential to improve knowledge, adherence to TTD consumption, and Hb levels as an effort to prevent anemia in female adolescents.